1994
DOI: 10.1007/bf00006806
|View full text |Cite
|
Sign up to set email alerts
|

Algae enhancing musty odor production by actinomycetes in Lake Kasumigaura

Abstract: The effect of algae on the production of musty-smelling compounds by actinomycetes was studied. Streptomyces spp., causing intensive musty odor, were isolated from hypertrophic Lake Kasumigaura and cultured in association with algae from the same lake. Isolate E and I effectively utilized the cyanobacteria, Microcystis aeruginosa and Anabaena spiroides, and the diatom, Synedra acus, as a carbon source and produced a musty-smelling 2-methylisoborneol in the shaken sediment cultures. High populations of algae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…As early as 1985, Wood and coworkers (107) demonstrated that natural reservoir water did not support geosmin production by Streptomyces albidoflavus and other isolates but required a source of enrichment such as found in sediment material and plant debris. In a later study, Sugiura and coworkers (91) reported that sedimented cyanobacteria and diatom cells (Microcystis aeruginosa, Anabaena spiroides, and Synedra acus) also provided good substrates for VOC production by benthic streptomycete isolates (we note here that in cases where this involved the mineralization of geosmin/2-MIB-producing cyanobacteria, odor could originate from active streptomycete metabolism and/or the release of cell-bound VOCs from the decaying cyanobacteria cells [see below]). As a further significant complication, optimal conditions vary among taxa, and in some cases even nutrient-poor environments can support VOC production by some actinomycetes.…”
Section: Tracing Geosmin and 2-mib Producersmentioning
confidence: 90%
See 2 more Smart Citations
“…As early as 1985, Wood and coworkers (107) demonstrated that natural reservoir water did not support geosmin production by Streptomyces albidoflavus and other isolates but required a source of enrichment such as found in sediment material and plant debris. In a later study, Sugiura and coworkers (91) reported that sedimented cyanobacteria and diatom cells (Microcystis aeruginosa, Anabaena spiroides, and Synedra acus) also provided good substrates for VOC production by benthic streptomycete isolates (we note here that in cases where this involved the mineralization of geosmin/2-MIB-producing cyanobacteria, odor could originate from active streptomycete metabolism and/or the release of cell-bound VOCs from the decaying cyanobacteria cells [see below]). As a further significant complication, optimal conditions vary among taxa, and in some cases even nutrient-poor environments can support VOC production by some actinomycetes.…”
Section: Tracing Geosmin and 2-mib Producersmentioning
confidence: 90%
“…As previously noted, the relative amounts of these fractions can vary among and within species, while cell-bound VOCs can be transferred rapidly into the dissolved form. One major mechanism for this is via cell degradation by heterotrophic microorganisms (which could include both producers and nonproducers, e.g., fungi and streptomycetes [90,91]). This process, for example, liberates geosmin from the cyanobacterial cell protein matrix.…”
Section: Intra-and Extracellular Voc Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment and mud may provide abundant nutrients such as carbon and nitrogen sources (Vallentyne and Bidwell, 1956) to support geosmin production (Wood et al, 1985). Additionally, the Streptomyces isolated from sediment may effectively utilize cyanobacteria as carbon sources, thereby generating a musty odor (Sugiura et al, 1994).…”
Section: Sediment Characterizationmentioning
confidence: 99%
“…This might cause the cyanobacteria to distribute to every portion of water from the sediment sample. Sugiura et al (1994) revealed actinomycetes around the colonies of phytoplankton by photomicrograph at a magnification 9400. An optical microscope allowed observation of a shape near 1 lm or larger of filamentous material from actinomycetes, although it could not identify the materials to be unicellular rods or fragments of actinomycetes, as identified by Nielsen et al (2006).…”
Section: Resultsmentioning
confidence: 99%